Novel TOP3A Variant Associated With Mitochondrial Disease: Expanding the Clinical Spectrum of Topoisomerase III Alpha–Related Diseases. (6th August 2022) - Primiano, Guido; Torraco, Alessandra; Verrigni, Daniela; Sabino, Andrea; Bertini, Enrico; Carrozzo, Rosalba; Silvestri, Gabriella; Servidei, Serenella
Abstract : Objectives: Topoisomerase III alpha plays a key role in the dissolution of double Holliday junctions and is required for mitochondrial DNA (mtDNA) replication and maintenance. Sequence variants in the TOP3A gene have been associated with the Bloom syndrome–like disorder and described in an adult patient with progressive external ophthalmoplegia. The purpose of this report is to expand the clinical phenotype of the TOP3A -related diseases and clarify the role of this gene in primary mitochondrial disorders. Methods: A 44-year-old woman was referred to our hospital because of exercise intolerance and creatine kinase increase. Muscle biopsy and a targeted next-generation sequencing (NGS) analysis were performed. Results: A histopathologic assessment documented a mitochondrial myopathy, and a molecular analysis revealed a novel homozygous variant in the TOP3A gene associated with multiple mtDNA deletions. Discussion: This case suggests that TOP3A is one of the several nuclear genes associated with mtDNA maintenance disorder and expands the spectrum of its associated phenotypes, ranging from a clinical condition defined Bloom syndrome–like disorder to canonical mitochondrial syndromes.